75 Kidney trajectory charts to guide management of reduced kidney function in general practice: a randomised controlled scenario study. (4th December 2019) - Guppy, Michelle; Glasziou, Paul; Doust, Jenny; Beller, Elaine; Flavel, Richard
Abstract : Objectives: Current chronic kidney disease (CKD) management guidelines use absolute estimated glomerular filtration rate (eGFR) values to define stages of disease, which may lead to both overdiagnosis and underdiagnosis. An alternative is a percentile chart of kidney function (measured as eGFR) compared to age. This study examined the usefulness of this chart in General Practice to appropriately diagnose patients with declining kidney function. Methods: This was a randomized controlled scenario study. A survey with questions about management of CKD was sent to a stratified, random sample of Australian General Practitioners (GPs). GPs were asked how they would diagnose and manage 2 patient cases. GPs were randomized to receive the cases either with a 'kidney trajectory chart' to aid in the decision making process, or initially without the chart, and then subsequently with the chart. Case 1 was an elderly woman with mild reduction in her kidney function, in the '3a CKD' stage, who was in the 50 th percentile for her age. Case 2 was a younger Aboriginal man who would not be considered to have kidney disease by the standard definitions, but who had kidney function in the 5 th percentile for his age. Results: Four hundred and seventy-two GPs participated in the study. Without the chart, GPs were unclear as to whether the case of the elderly woman with mild reduction in kidney function had a clinical problem with her kidneys (45% thought it likely, 12% were unsure, and 42% thought it unlikely), and they were similarly unclear as to whether she met the definition for disease. After viewing the kidney trajectory chart, 13% of GPs changed their opinion to indicate the patient was unlikely to have a clinical problem with her kidneys. The factor that influenced this the most was whether they could read the chart correctly. Other factors (age, length of practice, rurality, number of GPs at the practice, qualifications), did not influence this result. For case 2 (younger Aboriginal man with eGFR within the normal reference range, ) without the chart, 67% of GPs thought he did not meet the definition for disease, and they were unclear about whether he had a clinical problem with his kidneys (44% thought it likely, 12% were unsure, and 44% thought it unlikely). However after viewing the chart, 39% of GPs changed their opinion to indicate he was likely to have a clinical problem with his kidneys. Again the factor that influenced this the most, was the correct interpretation of the graph. Conclusions: The use of a 'kidney trajectory chart' in this study has shown the potential to correctly classify a patient who may have been otherwise underdiagnosed for kidney disease. It also shows the potential for preventing overdiagnosis in the case of an elderly patient with mild decline of kidney function. Further exploration of why GPs might think this type of patient doesn't have a clinical problem with their kidneys needs to be explored.